Pengaruh latihan circuit traning daya tahan untuk meningkatkan kesegaran jasmani pemain sepakbola u-12 SSB abhiseva Bengkulu tengah: The effect of endurance circuit training exercises to improve the physical fitness of U-12 soccer players at SSB Abhiseva Bengkulu, Central Bengkulu - Xoterik Erik; Syafrial; Bogy Restu Ilahi (Universitas Bengkulu, 2023)
ABSTRACT Xoterik (2018) : The Effect of Endurance Circuit Training Exercises to Improve Physical Freshness of U-12 Football Players at SSB Abhiseva Bengkulu Tengah. The purpose of this study is to determine whether U-12 soccer players at SSB Abhiseva Bengkulu Tengah are more physically fit after participating in endurance circuit training.The experimental approach is the research strategy utilized in this study.Twenty people, all U-12 players from Abhiseva Central Bengkulu, participated in this study.The findings of this study can be seen, with an increase in the average score of 15.12 following treatment with the Endurance Circuit Training Training Method from the initial value of 11.00.In addition to the increase in the average value of the final test (Post-Test), the analysis of the data description reveals that in the initial test, there were no samples with a Physical Freshness Level value. As many as 3 people (15%) received a very poor classification, 16 people (80%) received a poor classification, 1 person (5%) received a moderate classification, and no players received good or excellent classifications.In the meantime, scores increased on the final test (Post-Test), with as few as three people (15 percent) falling into the